Perceived public alarm and comprehension of risk communication messages about Lassa fever in Nigeria: a gauge of the risk communication model - Ben-Enukora, Charity Amaka; Oyero, Olusola; Okorie, Nelson; Ejem, Agwu Agwu; Omowale, Adelabu Toafeek (Frontiers in Communication, 2023)
Introduction Lassa fever constitutes a threat to the public health system in Nigeria with the reoccurring annual epidemics and its attendant risk communication intervention challenges. Objective This study examined the influence of public alarm (if any) on respondents' comprehension of risk communication messages about the most common host of the Lassa virus, modes of transmission, risk factors, and protective measures for Lassa fever. The risk communication model (mental noise hypothesis) served as the benchmark for measuring respondents' perceptions in the most endemic states in Nigeria. Method The study adopted a quantitative approach, using the survey method. Data for this study were collected from 653 respondents through a structured questionnaire. Respondents were selected through a multi-stage sampling technique. Frequency tables were used to profile the respondents' characteristics and key variables while regression coefficients were used to draw inferences. Results The study found a high level of perceived public alarm among the respondents but maximum attention was paid to risk communication messages amid the high level of anxiety. Knowledge of the common Lassa virus-host, modes of transmission, risk factors, and risk reduction measures was adequate irrespective of the high level of perceived public alarm. Public alarm significantly influenced audience comprehension of the risk information about Lassa fever in Ebonyi and Ondo at r2 = 0.040 and 0.076, at p < 0.05 but not in Edo state at r2 = 0.010, at p > 0.05. Conclusion The authors conclude that devoting adequate attention to outbreak communication messages amid a high level of anxiety could lead to improved knowledge of infectious diseases.